THERMODEFORMATIONAL CONDUCTIVITY TRANSIENTS IN NICKEL-COMPENSATED SILICON UNDER PULSED HYDROSTATIC PRESSURE - R.Khamidov; A.Suvanov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The dynamic response of nickel-compensated n-type silicon (n-Si:(P,Ni)) to rapid hydrostatic pressure changes is investigated. When pressure is applied at high rates (∼0.2 GPa/s), a pronounced transient conductivity effect is observed, distinctly different from the equilibrium static piezoresistance. Following a pressure step, the sample current initially surges beyond the static equilibrium value, peaks within 2-5 seconds, and subsequently relaxes to the static level while pressure is held constant. This phenomenon is attributed to coupled thermodeformational effects: hydrostatic compression induces both electronic deformation and adiabatic heating of the pressure-transmitting medium. The temperature rise, estimated at ΔT ≈ 8-10 K for ΔP = 0.6 GPa, causes additional thermal ionization of deep nickel levels, resulting in excess conductivity. The relaxation process corresponds to thermal equilibration as the sample cools to ambient temperature.